Preparation Model Of The Indicative Ceiling District In Support Of The Council Development Plan Case Study In The District Of Majalengka - Boy Tagajagawani (International Journal of Educational Research & Social Sciences, 2021)
On the study models the preparation of the ceiling inidikatif district aims to get the standard model in the contrive pegu indicative districts in favor of a council development plan in the district of majalengka. Methodology this research uses a qualitative descriptive approach, with the primary data collection method and skuder through interviews and document study. The results of this study produced a model of a standard preparation of the indicative ceiling district as standard in musnyawarah development plan. The results of this model can be used as a policy area majalengka regency in the preparation of development plans to the budget-setting process in the indicative ceiling district in accordance with the proportional region respectively in the district of majalengka.